Financial planning using rule based expert system - Qurratu Ain, Roslan (2013)
Financial Planning Application is a web-based application that implemented rule based technique. The idea behind this project development is when too many Malaysian, mostly young already in declared to bankruptcy. Most of the problem is when people cannot manage the personal financial well. This application develops to help our Malaysian to more careful with expenses every day. By using Rule Based Expert Application technique, this application will generate a suggestion budget per month expenses. In this application, the priority is must clear all the debt and have some saving. This application already scope into fresh graduated student in first-year work in industry. By answering eleven (11) questions, this application will generate some suggestion for financial. This application complete developed by guideline from the Rapid Application Development (RAD) software process that very effective to finish this development process. For this Financial Planning Application have an expert from Agensi Kaunseling dan Pengurusan Kewangan (AKPK) as a guide line on the percentage for every categories which are 10% for saving, 40% for loan and 50% for expenses. To summary the result of this application, salary RM 2500 and above are required to full fill all the requirement with enough others spending. However, salary below RM 2500 must reduce one or more of entire requirement to get the suitable expenses others spending.